Coping with the 'coffee crisis' in Central America: the role of the Nicaraguan Social Safety Net Programme - Maluccio, John A. (International Food Policy Research Institute, 2004)
The Nicaraguan Red de Proteccion Social (RPS) suggests that successful safety nets can protect the most affected by crisis without abandoning conditionality." -- from Text